Kualitas Selai Lembaran dengan Kombinasi Daging Buah Alpukat dan Bubur Kolang Kaling - Tanggara, Evangelista Cannola; Purwijantiningsih, Ekawati; Swasti, Yuliana Reni (Pro Food, 2025)
Sheet jam is a food made from fruit pulp that is dried at a temperature of around 50-65oC with a drying time ranging from 6 to 24 hours  depending on the raw materials used. In this study, avocado flesh was used do to its nutritional advantages  and serve as a source of pectin, as well as in combination with kolang kaling as a gelling agent in sheet jam. This study aims to determine the effect of the combination of avocado flesh and kolang kaling pulp on the quality of sheet jam based on chemical, physical, microbiological, and organoleptic properties and to determine the right combination between avocado flesh and kolang kaling pulp to obtain sheet jam results with the best quality. This study used a Completely Randomized Design (CRD) with 4 combination treatments of avocado flesh and kolang kaling pulp, namely the Control treatment 100:0; treatment A 95:5; treatment B 90:10; and treatment C 85:15. The results showed that the combination of avocado flesh and kolang kaling pulp had a significantly different effect on quality of sheet jam including moisture content, ash content, insoluble fiber content, soluble fiber content, total soluble solids, and texture analysis,  but did not have a significant effect on color analysis and microbiological tests, including total plate count and yeast and mold count. The optimal combination of avocado flesh and kolang kaling pulp to produce sheet jam with the best quality was 85% avocado flesh and 15% kolang kaling pulp.